PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PUSKESMAS SP IV PRAFI MANOKWARI PAPUA BARAT - Syukur, Reza Zainal; Nurlaela, Nurlaela; Nurwidianto, Nurwidianto (Cakrawala Management Business Journal, 2023)
ABSTRACT This study aims to determine the influence of leadership style and work discipline on employee work productivity both partially and simultaneously. The analytical technique used in this study is quantitative analysis. The sample in this study was 41. The sampling technique used is in the form of non-propability sampling of primary data used in the form of questionnaires. Secondary data are obtained from journals and books related to research. The method used is multiple linear regression analysis using SPSS statistical software. Based on the results of the analysis on the variables of leadership style and work discipline have a partial effect on employee work productivity. The results of the Anova test analysis of the variables of leadership style and work discipline have a simultaneous effect on employee work productivity at the Sp IV Prafi Manokwari Health Center, West Papua. The suggestion of the leader of the Sp IV Health Of centers is to pay more attention to the performance of the bituhanya by monitoring regularly as well as being transparent in giving awards to motivate employees and providing sanctions that make employees not feel degraded.